The Active Role of Parents in the Socio-Emotional Development of Preschool Children - Fazrin, Intan; Nisa, Khoirun; Chusnayataini, Arina; Saputra, Zainal Andy (Universitas STRADA Indonesia, 2025)
The preschool period is a golden era for development, where social and emotional skills determine a child's future ability to interact and manage emotions. This study aims to analyze the relationship between active parental involvement and the socio-emotional development of preschool children at Dharma Wanita Persatuan 1 Kindergarten in Kemulan Village. Using a descriptive correlational design with a cross-sectional approach, the study employed a total sampling technique involving 55 parent respondents from the institution. Data were collected through a parental role questionnaire and developmental observation sheets, subsequently analyzed using the Spearman’s Rank Correlation Test. Results revealed a p-value of 0.019, confirming a significant relationship where higher parental engagement leads to superior emotional outcomes. It is recommended that educational institutions and community programs, such as Bina Keluarga Balita, enhance parental literacy to create a supportive ecosystem that fosters children's independence and emotional regulation